Protocol: a 'One health' two year follow-up, mixed methods study on antibiotic resistance, focusing children under 5 and their environment in rural India. (December 2015) - Stålsby Lundborg, Cecilia; Diwan, Vishal; Pathak, Ashish; Purohit, Manju; Shah, Harshada; Sharma, Megha; Mahadik, Vijay; Tamhankar, Ashok
Abstract Background Antibiotic resistance has been referred to as 'the greatest malice of the 21st century' and a global action plan was adopted by the World Health Assembly in 2015. There is a wealth of independent studies regarding antibiotics and resistant bacteria in humans, animals and their environment, however, integrated studies are lacking, particularly ones that simultaneously also take into consideration the health related behaviour of participants and healthcare providers. Such, 'One health' studies are difficult to implement, because of the complex teamwork that they entail. This paper describes the protocol of a study that investigates 'One health' issues regarding antibiotic use and antibiotic resistance in children and their environment in Indian villages. Methods/Design Both quantitative and qualitative studies are planned for a cohort of children, from 6 villages, and their surrounding environment. Repeated or continues data collection is planned over 2 years for quantitative studies. Qualitative studies will be conducted once. Studies include parents' health seeking behavior for their children (1–3 years of age at the onset), prescribing pattern of formal and informal healthcare providers, analysis of phenotypic antibiotic resistance ofEscherichia coli from samples of stool from children and village animals, household drinking water, village source water and waste water, and investigation on molecular mechanisms governing resistance. Analysis of interrelationship of these with each other will also be done as basis for future interventions. Ethics approval has been obtained from the Institutional Ethics Committee R.D. Gardi Medical College, Ujjain, India (No: 2013/07/17-311). Discussion The findings of the study presented in this protocol will add to our knowledge about the multi-factorial nature of causes governing antibiotic use and antibiotic resistance from a 'One health' perspective. Our study will be the first of its kind addressing antibiotic use and resistance issues related to children in a One-health approach, particularly for rural India.